2015
DOI: 10.4045/tidsskr.14.1194
|View full text |Cite
|
Sign up to set email alerts
|

Er en belastet barndom knyttet til kortere telomerer?

Abstract: OversiktsartikkelEr en belastet barndom knyttet til kortere telomerer? 1356 -60 Ane Brandtzaeg Naess ane.b.naess@hotmail.com Universitetet i Oslo Anna Luise KirkengenAllmennmedisinsk forskningsenhet Institutt for samfunnsmedisin Norges teknisk-naturvitenskapelige universitet og Institutt for samfunnsmedisin Universitetet i Tromsø -Norges arktiske universitet HOVEDBUDSKAP I mange studier ser man en sammenheng mellom belastende barndomsforhold og kortere telomerer, selv om forskningsgrunnlaget ikke er entydig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Several different lines of research have found links between adverse life experiences in the early years of life and adult telomere length (1113). These studies are difficult to interpret given that adversities tend to co-occur.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several different lines of research have found links between adverse life experiences in the early years of life and adult telomere length (1113). These studies are difficult to interpret given that adversities tend to co-occur.…”
Section: Discussionmentioning
confidence: 99%
“…For example, perceived neighborhood quality (46), anxiety (7), exposure to intimate partner violence (8, 9), and being the primary caregiver of a child with a chronic condition (10) are all inversely correlated with telomere length, as typically measured during adulthood. Associations between telomere length and adverse early life experiences have also been observed (1113). Adults reporting physical or emotional neglect during childhood had shorter telomeres than their counterparts who did not report any childhood maltreatment (14).…”
Section: Introductionmentioning
confidence: 95%